Functionalized calcium orthophosphates (CaPO4) and their biomedical applications. Issue 47 (18th November 2019) - Dorozhkin, Sergey V.
Abstract : Due to the chemical similarity to natural calcified tissues (bones and teeth) of mammals, calcium orthophosphates (abbreviated as CaPO4 ) appear to be good biomaterials for creation of artificial bone grafts. Abstract : Due to the chemical similarity to natural calcified tissues (bones and teeth) of mammals, calcium orthophosphates (abbreviated as CaPO4 ) appear to be good biomaterials for creation of artificial bone grafts. However, CaPO4 alone have some restrictions, which limit their biomedical applications. Various ways have been developed to improve the properties of CaPO4 and their functionalization is one of them. Namely, since surfaces always form the interfaces between implanted grafts and surrounding tissues, the state of CaPO4 surfaces plays a crucial role in the survival of bone grafts. Although the biomedically relevant CaPO4 possess the required biocompatible properties, some of their properties could be better. For example, functionalization of CaPO4 to enhance cell attachment and cell material interactions has been developed. In addition, to prepare stable formulations from nanodimensional CaPO4 particles and prevent them from agglomerating, the surfaces of CaPO4 particles are often functionalized by sorption of special chemicals. Furthermore, there are functionalizations in which CaPO4 are exposed to various types of physical treatments. This review summarizes the available knowledge on CaPO4 functionalizations and their biomedical applications.